Evaluación del Vetiver (vetiveria zizanioides) para la disminución de Metales Pesados (pb, cd), en el Canal de Riego Latacunga – Salcedo – Ambato en el Sector Samanga. - Cuji Quingaluisa, Janeth Katerine (2017)
This searching was realized through a Vetiver hydroponic planting, with the followings treatments: T1, witness (without plants of vetiver), T2 - 50 plants of vetiver (V50), T3, 100 plants of vetiver (V100). It worked both the evaluation of the behavior of the plants and the grade of absorption of heavy metals (Cd, Pb). The experimentation lasted six months using plastic tanks with 100 liters of capacity and one system of recirculation of water from the irrigation canal. The analysis of heavy metals present in the water was realized in a Spectrophotometer of atomic absorption with graphite furnace detector of make PG instruments. The results obtained indicate significate differences p<0,05 between treatments, resulting from between a 43 to 80,4 % according to the density of planted plants (50 plants and 100 plants/tank respectively), while in cadmium it varies from 46.2% to 70.7%. The searching was realized with the objective of improving the quality of water in agricultural irrigation waterway Latacunga-Salcedo-Ambato to help to purify water in the agricultural production and the sector cattle also to avoid the farming contaminated and diseases in animals at this area. The result obtains in this researching showing the decreased of heavy metals like cadmium and lead for absorption of vetiver plants.